Base-Promoted Michael Reaction Concomitant with Alkylation of Cyclic-1,3-diones, an Efficient Approach to 2-Substituted Vinylogous Esters - De, Subhadip; Kinthada, Lakshmana K.; Bisai, Alakesh (Synlett, 2012)
Vinylogous esters can be synthesized by a base-promoted Michael reaction concomitant with alkylation of the cyclic 1,3-dione substrate. The methodology provides a wide range of 2-substituted vinylogous esters in good to excellent yields.
Keywords: vinylogous esters; cyclohexenones; Michael reaction; alkylation; diones